Permafrost Degradation and Concomitant Hydrological Changes Dominated by Anthropogenic Greenhouse Gas Emissions in the Northeastern Tibetan Plateau - Pei Fang; Taihua Wang; Dawen Yang; Jingjing Yang; Lihua Tang (Geophysical Research Letters)
Abstract Permafrost degradation on the Tibetan Plateau (TP) has profound impacts on hydrological processes, yet the responses of permafrost hydrology to different climate forcings remain unclear. Here we integrate outputs from global climate models with a watershed cryospheric‐hydrological model to provide the first quantitative attribution analysis to examine the responses of permafrost hydrology to anthropogenic and natural forcings in the source region of the Yellow River, northeastern TP. Our results confidently attribute frozen ground degradation to anthropogenic greenhouse gases (GHG), leading to permafrost area decline by 3,398.4 km2/10a during 1960–2019, while aerosols exhibit a slight mitigating effect. GHG emissions also drive concomitant hydrological changes, including increased subsurface runoff and winter runoff ratio. They also reduce streamflow seasonality, particularly in regions where permafrost degrades severely. Our study provides critical insights for understanding permafrost and hydrological processes under climate change, highlighting the importance of effective emission reduction and adaptive water resources management strategies.